Unraveling the ferroelectric switching mechanisms in ferroelectric pure and La doped HfO2 epitaxial thin films. (May 2023) - Silva, Alexandre; Fina, Ignasi; Sánchez, Florencio; Silva, José P.B.; Marques, Luís; Lenzi, Veniero
Abstract: Epitaxial orthorhombic phase La doped HfO2 films are promising for achieving robust ferroelectric polarization without wake-up effect. However, lowering the coercive field is crucial for achieving low-power memory devices. In this work, we have investigated the influence of the La content effect on the structural and ferroelectric properties of epitaxial HfO2 thin films. We show that while the remanent polarization is optimum for 2–5 at. % La-doped HfO2 films, the coercive field is decreased with La doping. The experimental work is supported by density functional theory (DFT) calculations which show that the polarization switching in epitaxial La:HfO2 films can be understood based on the synergetic contribution of the presence of a non-ferroelectric monoclinic phase and the La doping itself that causes a reduction of the nucleation and DW motion energy barriers for the crossing path, which makes it more probable than the non-crossing one. Highlights: The coercive field (Ec) in La:HfO2 epitaxial thin films is decreased with La doping. DFT shows that ferroelectric switching barriers of o -phase HfO2 decrease in presence of o/m -phase interface and La doping. Doping reduces nucleation and DW motion energy barriers for crossing path, making it more probable than non-crossing one.